DEVELOPMENT OF PHYSICS TEACHING TOOLS ON THE MATERIAL OF HARMONIC MOTION OSCILLATION ON SPRINGS - Shofiyah, Analiatus; Suprianto, Suprianto; Wildani, Arin (Jurnal Pendidikan Matematika dan IPA, 2026)
This study aims to develop an interactive teaching aid using Arduino Uno and MPU6050 accelerometer sensor to make it easier for students to understand the concept of simple harmonic motion (SHM) on springs. The tool is designed to detect vertical oscillatory motion, calculate the oscillation period (T) and spring constant (k) automatically, and display the results in real-time on an I2C LCD screen. This study employs a research and development (R&D) method using the ADDIE model, focusing on the development stage. The tool developed is designed to detect vertical spring motion, measure the period (T) and spring constant (K) values, and display them automatically via a 12C LCD screen. The validation process carried out by two material experts resulted in a mean of 81% in the very feasible qualification, and validation by two media experts resulted in 97% also in the very feasible category. This tool is considered effective, efficient, and contextual as a solution-based and technology-assisted physics learning tool. Calibration was carried out to compare the measurement results using the sensor with the manual method, and the results showed a high level of accuracy and a relatively high data difference. In addition, testing was carried out using two springs with different diameters, namely 1 mm and 1.5 mm, to observe the effect of physical characteristics on the spring constant value and oscillation period. The experimental results showed that the pegs with a smaller diameter had a larger constant and a shorter period, while the spring with a larger diameter produced a longer period. Thus, this tool is not only technically feasible, but also effective for visualizing the concept of spring oscillation in physics learning.